2018
DOI: 10.1136/archdischild-2017-313715
|View full text |Cite
|
Sign up to set email alerts
|

Using a composite morbidity score and cultural survey to explore characteristics of high proficiency neonatal intensive care units

Abstract: Cultural, environmental and cognitive characteristics vary among NICUs perhaps more than traditional CQI methodology and PBPs, possibly explaining the inconstancy of VLBW infant morbidity reduction efforts. High proficiency NICUs foster spirited team work and camaraderie, sustained learning opportunities and support of favourable staffing that allows problem solving and widespread involvement in CQI activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…While differing outcomes can be simply due to differing case‐mix, other factors may contribute. US researchers developed a composite morbidity and mortality score (the Benefit Metric) as a measure of performance . Each NICU completed a detailed cultural survey to determine the characteristics of better‐performing NICUs .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While differing outcomes can be simply due to differing case‐mix, other factors may contribute. US researchers developed a composite morbidity and mortality score (the Benefit Metric) as a measure of performance . Each NICU completed a detailed cultural survey to determine the characteristics of better‐performing NICUs .…”
mentioning
confidence: 99%
“…US researchers developed a composite morbidity and mortality score (the Benefit Metric) as a measure of performance . Each NICU completed a detailed cultural survey to determine the characteristics of better‐performing NICUs . The score was applied retrospectively to 39 NICUs caring for 58 272 very low birthweight infants from 2000 to 2014.…”
mentioning
confidence: 99%
“…For QI efforts to be effective in a healthcare service, it is vital to have clear leadership combined with an environment where frontline staff are empowered to actively engage in the process . There is evidence of positive cultural change in this project's NICU, with one intervention point focused on enabling nurses and respiratory therapists to speak up with their concerns.…”
mentioning
confidence: 99%
“…Kaempf et al 7 explain these centre variations through differences in contextual factors. The authors compare the characteristics of low and high performing NICUs caring for very low birthweight infants using a quantitative measure of performance, a risk-adjusted composite morbidity score called the Benefit Metric and the results of a 103 question contextual factors survey.…”
mentioning
confidence: 99%
“…Our outcomes undergo consistent review by senior leadership and are reported to the Board of Trustees. In response to questions raised by Kaempf,7 the secret sauce may lie in establishing systems that promote the culture of quality and safety rather than waiting for a reduction in morbidity to promote happier staff. Contextual factors play a critical role in enhancing performance and should be studied and reported in quality publications to allow readers to determine the applicability and generalisability of interventions to their local context.…”
mentioning
confidence: 99%